ChemInform Abstract: Rhodium‐Catalyzed Alkene Difunctionalization with Nitrenes. Issue 46 (October 2016) - Ciesielski, Jennifer; Dequirez, Geoffroy; Retailleau, Pascal; Gandon, Vincent; Dauban, Philippe
Abstract: A broad spectrum of 1, 2‐amino alcohols and 1, 2‐diamines is synthesized as is demonstrated for a series of selected examples.